Development and validation of an electroanalytical methodology for determination of isoniazid and rifampicin content in pharmaceutical formulations - Katia Christina Leandro; Juliana Machado de Carvalho; Luiz Fernando Giovanelli; Josino Costa Moreira (Universidade de São Paulo, 2009)
Tuberculosis remains a major public health problem, especially in developing countries. Brazil presents the largest number of cases in Latin America and is among the 22 countries considered priorities by the World Health Organization (WHO). The Rio de Janeiro state has the largest number of cases registered in the country. The treatment of patients, commonly, makes use of the drugs isoniazid and rifampicin for six months. This study aimed to develop and validate an electroanalytical methodology, using the technique of differential pulse voltammetry for the determination of these drugs in the associated form, in order to evaluate the quality of medicines distributed in the state of Rio de Janeiro. The potential reduction for the isoniazid and rifampicin were -1.10 and -0.90 V. The developed and validated electroanalytical method presented a linear range of 0.25 to 1.25 mg/L to isoniazid, limits of detection and quantification of 0.05 and 0.14 mg/L, and recovery of 98.2 ± 0.4%; a tracking linear of 0.40 to 2.00 mg/L for rifampicin, with limits of detection and quantification of 0.07 and 0.19 mg/L and recovery of 95.8 ± 0.6%. Six lots of medicines from two pharmaceutical companies were analyzed. Only one of the samples showed unsatisfactory levels of rifampicin. A tuberculose continua sendo um importante problema de saúde pública, especialmente em países em desenvolvimento. O Brasil apresenta o maior número de casos da América Latina, estando entre os 22 países considerados prioritários nas ações de controle da doença pela Organização Mundial da Saúde (OMS). No Brasil, o Rio de Janeiro é o estado com o maior número de casos registrados no país. O tratamento de doentes com tuberculose faz uso dos fármacos isoniazida e rifampicina durante seis meses. O presente trabalho objetivou desenvolver e validar metodologia eletroanalítica, utilizando a técnica de voltametria de pulso diferencial, para a determinação desses dois princípios ativos na forma associada e avaliar a qualidade dos medicamentos distribuídos no estado do Rio de Janeiro. Os potenciais de redução para a isoniazida e rifampicina foram respectivamente -1,10 e -0,90 V. O método eletroanalítico desenvolvido e validado apresentou para a isoniazida faixa linear de 0,25 a 1,25 mg/L, limites de detecção e quantificação de 0,05 e 0,14 mg/L e recuperação de 98,2 ± 0,4%; para a rifampicina faixa linear de 0,40 a 2,00 mg/L, limites de detecção e quantificação de 0,07 e 0,19 mg/L e recuperação de 95,8 ± 0,6%. Foram analisados 6 lotes de medicamentos de dois laboratórios farmacêuticos. Apenas uma das amostras apresentou teor de rifampicina insatisfatório.